International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) [Datensatz] - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

On the (Limited) Generalization of MasterFace Attacks and Its Relation to the Capacity of Face Representations - Terhörst, Philipp; Bierbaum, Florian; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (International IEEE Joint Conference on Biometrics, IJCB 2022, Abu Dhabi, United Arab Emirates, October 10-13, 2022)

On Evaluating Pixel-Level Face Image Quality Assessment - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Damer, Naser; Kuijper, Arjan (2022 30th European Signal Processing Conference (EUSIPCO))

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Franz Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Teaching and Learning Data-Driven Machine Learning with Educationally Designed Jupyter Notebooks - Fleischer, Franz Yannik; Biehler, Rolf; Schulte, Carsten (Statistics Education Research Journal)
This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out the machine learning technically and reasoning about bias in the data, different data preparation steps, the application context, and the resulting decision model. Furthermore, the context of the study and the theoretical backgrounds are presented.
Keywords: Education; Statistics and Probability

Einleitung - Priesching, Nicole; Pahlke, Georg (Lorenz Jaeger als Seelsorger)

Lorenz Jaeger als Seelsorger

Einleitung - Priesching, Nicole; Kasprowski, Christian (Lorenz Jaeger als Kirchenpolitiker)

Einleitung - Priesching, Nicole; Pahlke, Georg (Lorenz Jaeger als Seelsorger)

„Ich klage an!“ Pfarrer Heinrich Ostermann am 19. Dezember 1945 an Erzbischof Lorenz Jaeger - Priesching, Nicole (Lorenz Jaeger als Seelsorger)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

Die Theologie und ihre Akteure" & "Praktizierte Glaubensreflexion als Erkenntnisort der Theologie - Grössl, Johannes (Die Bedeutung von Gläubigen für die Theologie)

Gottes Immanenz denken – auch im personalen Theismus? - Grössl, Johannes (Mit dem Herzen denken. Konturen einer leidenschaftlichen Theologie der Welt [FS Roman Siebenrock])

Erkenntnis durch Offenbarung als Gefahr für menschliche Autonomie? - Grössl, Johannes (Problemfall Offenbarung. Grund – Konzepte – Erkennbarkeit)

Extra narrationem nulla salus. Perspektiven eines narrativitätstheoretischen Ansatzes für die christliche Soteriologie - Grössl, Johannes; Kronau, Johannes (Münchner Zeitschrift für Katholische Theologie)

Beethoven in the House: Digital Studies of Domestic Music Arrangements - Page, Kevin R.; Kepper, Johannes; Siegert, Christine; Hankinson, Andrew; Lewis, David (Music Encoding Conference Proceedings 2021)
Performance of music in the home was the means by which most works were received before the advent of audio recordings and broadcasts, yet the notation sources that form our primary record of this culture have not been the subject of comprehensive or methodical study. Choices made by arrangers adapting music for domestic consumption – of instrumentation, abbreviation, or simplification – reflect the musical life of the 19th century, and can inform our understanding alongside contemporary accounts such as newspapers, adverts, and diaries. This position paper gives the background, motivation, and proposed approach of research currently being undertaken within the Beethoven in the House project. This will include a study of Steiner editions of Beethoven’s 7th and 8th Symphonies and Wellingtons Sieg, making a detailed comparison between arrangements, systematically identifying a core common to multiple versions, and asking if this reflects the stated values of the publisher. A second survey will look for patterns across a larger sample of lesser-known and poorly catalogued scores, collating emergent indicators of arrangers’ motivations within a narrative of the domestic market – the music industry of its day. Both studies will innovate digital methods which characterise arrangements as music encodings, including ‘sparse’ approaches to notation and annotation.
Keywords: BitH; mec-proceedings; mec-proceedings-2021

Encoding Genetic Processes II - Cox, Susanne; Kepper, Johannes (Music Encoding Conference Proceedings 2021)

A model for annotating musical versions and arrangements across multiple documents and media - Lewis, David; Shibata, Elisabete; Saccomano, Mark; Rosendahl, Lisa; Kepper, Johannes; Hankinson, Andrew; Siegert, Christine; Page, Kevin (9th International Conference on Digital Libraries for Musicology)
Keywords: BitH

Educational Management on regional levels. Implications for vocational education - Daniel-Söltenfuß, Desiree; Hagemeier, Daniel; Ludolph, Fabian

Die Konstruktion von Geschäftsmodellen für nachhaltiges Wirtschaften: (k)eine exklusive Aufgabe des Managements?! - Schlömer, Tobias; Kiepe, Karina; Thrun, Tim (Intrapreneurship)